Illness Perceptions And Its Effect On Anxiety And Symptoms Of Depression Hospitalization -diabetic Patients Undergoing Lower Extremity Amputation As A Model- - حميداني عيسى; رحماني أسماء (مجلة دراسات في سيكولوجية الانحراف, 2023)
The study aimed to reveal the effect of illness perception on Anxiety and Symptoms of depression hospitalization in diabetic patients undergoing lower limb amputation. The sample of the study encompasses randomly selected 32 individuals with Lower Limb Amputation who live in Khenchela. Using the relational descriptive method. The study relied on two measures of the Illness Perceptions Questionnaire (Brief IPQ), and Hospital Anxiety and Depression (HADS). The study results were as there is a relationship between Sex, economic status, educational level, and cognitive representations with both anxiety and depression. In addition, there is an effect of each of the cognitive representations in combination with age on anxiety, as well as the effect of economic status, educational level, and gender on depression. Based on these results, we recommend building treatment plans and programs to improve the nature of Illness perceptions and try to reduce the symptoms of anxiety and depression in diabetic patients undergoing lower limb amputation.